Pedagogical Accompaniment and Teaching Performance in the Primary Educational Institution of Minors nº 127 "San José", at the levels of Initial and Primary – district El Agustino - Cuellar Cajahuaringa , Hernán Elvis (2022)
Pedagogical Accompaniment and Teaching Performance in the Primary Educational Institution for Minors No. 127 "San José", at the levels of Initial and Primary - El Agustino district, its main objective is to determine the relationship between the study variables (Pedagogical Accompaniment and Teaching Performance) . Methodologically it is descriptive - correlational, non-experimental, transversal, quantitative. The population is made up of 56 teachers, applying the formula to a size of 49 teachers. Two Lickert-type instruments were designed then subjected to validity and reliability whose consistency was "good" based on the established parameters. The thesis concludes by showing that there is a strong positive correlation throughout the research, between the variables analyzed: Pedagogical Accompaniment and Teaching Performance, as well as between their dimensions respectively.